Visual Basic 2008 Recipes - Herman, Todd (Springer, 2017)
Visual Basic 2008 Recipes is a book of ready-made coding solutions for programmers who don't want spend a lot of time reading. Each chapter addresses a specific problem-domain such as multimedia, database access, XML manipulation, etc. Each chapter then presents a number of common problems, with a solution following each problem. Readers appreciate the recipe format, because they can look up a problem, read one to three pages, implement the solution, and then get on with their work. Recipe books are ideal for those who want to spend their days doing, not reading.